Business jet safety and accident study - Sears, R. W. (Cranfield University, 2013)
As world transport has grown in complexity, so has public pressure for safe flight. The scheduled airline industry has a consistently good safety record. Unfortunately, the business jet industry has not kept pace with the airline safety statistics and lags far behind. During safety surveys and reports over the past 5 years there has been increasing comment and concern over the perceived safety standards of business jets operations compared with normal scheduled airline services. The UK Civil Aviation Authority (CAA) has reported that based on flight hours flown, the fatal accident rate for smaller jet aircraft below 15 tonnes was twice that for large passenger aircraft (CAA 2006a). The CAA also identified that the majority of the accidents occur during the approach and landing phase of the flight. There is however, a lack of research concerning business jet operations. Due to the unique and varied style of operations, business jet flights have many factors that differentiate it from normal scheduled airline operations. Business jet accidents have been reported but they have not been further investigated for any overall causes. The study described in this thesis, a Grounded Theory analysis of accident data was conducted to develop a model of the factors that contributed to the accidents. The model that was developed demonstrated that Pilot skills, Command and Crew Resource management are the key central elements, with the ground organisations such as engineering and ground operations personnel as a contributory influence. As piloting skills were determined as a key factor in the accident statistics and the accident model, a simulator trial was also conducted to assess the manual flying skill levels of business jet pilots. The trial was both a challenging manual flying task and a profile that is included as part of the Pilot Skill test prior to the issue of a commercial pilot’s licence. The simulator trial confirmed that although all the pilots were correctly tested and certified commercial pilots, a significant proportion did not fly an accurate airspeed on approach within the CAA examination tolerances. The simulator trial data and the grounded theory model found that there are concerns for the piloting skills of business jet pilots in their ability to fly an accurate airspeed on approach. The results from this investigation yield findings concerning the piloting skill and accuracy of the business jet pilots that had not previously been identified. The results also emphasise the need to include adequate testing and supervision during business jet operations. It is recommended that further research be conducted to evaluate actual piloting skill and accuracy during the licence skill test.
Keywords: Accident Analysis; CRM; Piloting skills; Operational Environment; Control strategy; Simulator.